Fabrication of MgAl2O4 Spinel Scaffolds and Sonochemical Synthesis and Deposition of Hydroxyapatite Nanorods. Issue 5 (2nd March 2016) - Biswas, Papiya; Sharma, Anu; Krishnan, Manu; Johnson, Roy; Mohan, Mantravadi Krishna
Abstract : Hydroxyapatite (HAp) is one of the most emerging biocompatible ceramic widely used as scaffolds in various biomedical applications such as orthopedics and dentistry. In spite of the superior properties for biomedical applications, they exhibit poor mechanical properties. This has lead to the concept of fabricating composite out of bioactive and bioinert material to derive bioactivity in combination with desirable mechanical properties. In this study, bioinert magnesium aluminate (MgAl2 O4 ) spinel scaffolds are prepared through polymeric foam replication process followed by sintering. Sintered foams have exhibited good structural integrity and the stress–strain curves recorded during the uniaxial compression have shown a plateau indicating high‐energy absorption capability. Sonochemical process has been employed for the simultaneous synthesis and deposition of HAp formulation from the stoichiometric solution of precursors on the spinel scaffolds. Sonochemical process has resulted in the formation of phase pure HAp with unique morphology of nanorods coated throughout the three‐dimensional foam structures. Cytotoxicity evaluation of this new scaffold material has not shown any alteration in the viability, growth, and morphology of the cells. The new scaffold material thus developed is expected to have high potential for biomedical applications.